Two new species and new records of the genus Astenus from Madagascar (Coleoptera: Staphylinidae: Paederinae) - Janák, Jiří; Baňař, Petr (Zootaxa, 2021)
Two new species of the genus Astenus Dejean, 1833, A. ambohitantelyensis Janák & Baňař, sp. nov. and A. grebennikovi Janák & Baňař, sp. nov. from Madagascar are described and illustrated. New records of eleven additional species are presented.